Comprehensive investigation on isolation, quantification, and activity evaluation of salvianolic acids for injection based on improved dry load injection technology. Issue 8 (26th May 2022) - Gao, Jian; Zhou, Lin; Zhang, Lele; Luo, Xi; Fu, Zhifei; Pan, Guixiang; Xu, Qiang; Han, Lifeng
Abstract: In this work, an effective method for simultaneous isolation of eight compounds from Salvianolic Acids for Injection was developed by preparative high‐performance liquid chromatography based on improved dry load injection. Firstly, the chemical structures of the obtained compounds were identified by mass spectrometry and nuclear magnetic resonance spectra. Subsequently, a sensitive liquid chromatography‐tandem mass spectrometry method was established to precisely quantify the eight isolated target analytes. The quantitative results show salvianolic acid B as the most abundant component (460.06–514.68‰) and protocatechualdehyde (0.03–0.08‰) as the least. Finally, the antioxidant activities of the isolated compounds were further investigated. The 2, 2‐diphenyl‐1‐picrylhydrazyl‐scavenging assay indicated that (7′ R, 8′ S, 8″ R, 8′′′ R )‐epi‐salvianolic acid B had the lowest half‐maximal inhibitory concentration (5.05 μg/ml). This study reports on the development of an effective and rapid method for simultaneous isolation of multiple compounds from traditional Chinese medicine preparation, which could be used as reference compounds for further quality control and activities screening.